درجة إكتشاف الإشارة وعلاقتها بمستويات يقظة متخذي القرارات الإستراتيجية دراسة إستكشافية بعينة من المؤسسات الصغيرة والمتوسطة - اليمين, فالتة (Recherches économiques et managériales, 2014)
تهدف هذه الدراسة إلى تبيان أهمية استخدام بعض مفاهيم وإفتراضات نظرية اكتشاف الإشارة في تحديد درجة إكتشاف الإشارة عند عينة من متخذي القرارات الإستراتيجية في المؤسسات الصغيرة والمتوسطة، من خلال قياس قدراتهم الحسية والشعورية في تسجيل ورصد الإشارات الضعيفة، وقياس قدراتهم الإدراكية على فهم حقيقة هذه الإشارات ومدلولاتها العملية، في إطار خلفية من التداخل والفوضى التي يتميز بها محيط القرار. يريد الباحث أن يستكشف طبيعة العلاقة بين درجة يقظة متخذ القرارات الإستراتيجية، وقدرته على إكتشاف الإشارة. وقد أجريت الدراسة على عينة مؤلفة من (60) فردا تم تحليل البيانات باستخدام الحزمة الإحصائية( Statistical Package for the Social Sciences ) أمكن من خلالها الوصول إلى أن محيط اتخاذ القرار يتميز بإضطراب وتشويش في الإشارات. وأن متخذي القرارات الإستراتيجية على درجة متوسطة من القدرة على إكتشاف الإشارة. كما أن مستويات اليقظة تتأرجح بين الدرجة الكبيرة والدرجة المتوسطة. ودلت نتائج الإرتباط عن وجود ارتباط موجب وقوي عند مستوى أقل من الدلالة 1% . الكلمات الدالة: اليقظة،الإشارات الضعيفة، الإحساس، الإدراك، الفوضى، التشويش القرارات الإستراتيجية. Abstract :   This study aims to identify the importance of using some concepts and assumptions of the theory of detection signal to determine the different degrees of signal detection, at the strategic decision makers in small and medium enterprises, From the degrees of perceptual awareness and opportunities in the detection of weak signals of a hand, and precision degrees of consciousness of truth and meaning of this operational signals other hand, in an environment of  decision  characterized by  chaos and overlap, As is the case in any study the researcher wants to explore the nature of the relationship between the degree of vigilance of the strategic decision maker, and its ability to detect the signal . The study was conducted on a sample of (60) individuals, and using the statistical package (Statistical Package for the Social Sciences). The study came up with the following conclusions : - Environment decision is characterized by the vicinity of chaos and Noise in the signals . - The general trend indicates that the strategic decision-makers on the degree of medium from the signal detection . - The levels of vigilance of the strategic decision makers oscillate between the large and medium-class . - The results of correlation analysis indicated that the nature of the relationship between the degree of vigilance of the strategic decision maker and the degree of signal detection, correlation is positive and strong  and with moral significance at 1 % or less. Keywords : weak signals, strategic decisions, vigilance, sense, perception, chaos &Noise